2015
DOI: 10.1542/peds.2014-1653
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Inclusion Training in Pediatric Departments

Abstract: BACKGROUND AND OBJECTIVE: The diversifying US population of children necessitates assessing the diversity of the pediatric academic workforce and its level of cultural competency training. Such data are essential for workforce and educational policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 7 publications
(2 reference statements)
2
33
0
Order By: Relevance
“…Although diversity training is one of the more common interventions suggested and implemented in organizations broadly (Dobbin & Kalev, 2016) and in medical schools specifically (Mendoza et al, 2015; Rapp, 2006), we are aware of little empirical evidence regarding a sustained effect of diversity trainings on racial bias. Most evidence points to sustained improvement in cultural knowledge or information regarding diversity (e.g., Bezrukova, Spell, Perry, & Jehn, 2016; Majumdar, Browne, Roberts, & Carpio, 2004).…”
mentioning
confidence: 99%
“…Although diversity training is one of the more common interventions suggested and implemented in organizations broadly (Dobbin & Kalev, 2016) and in medical schools specifically (Mendoza et al, 2015; Rapp, 2006), we are aware of little empirical evidence regarding a sustained effect of diversity trainings on racial bias. Most evidence points to sustained improvement in cultural knowledge or information regarding diversity (e.g., Bezrukova, Spell, Perry, & Jehn, 2016; Majumdar, Browne, Roberts, & Carpio, 2004).…”
mentioning
confidence: 99%
“…6 Ninety percent of 131 US pediatrics chairs surveyed incorporate cultural competency training into their residency programs. 7 While the value of training residents to care for a diverse patient population is well established, we found no prior studies of interventions to address residents' readiness to respond appropriately to discriminatory comments. Some programs have identified strategies to help support residents when they encounter discriminatory comments in the workplace.…”
Section: Introductionmentioning
confidence: 82%
“…The U.S. PHO physician workforce has limited ethnic diversity with only 5–10% identified as African American or Hispanic despite a diversifying population of children within the United States. Other studies have shown that this limited ethnic diversity is also observed in general pediatric trainees, faculty, and leaders within departments of pediatrics with <10% in each group being African American, Hispanic, or Native American . Physician engagement with minority patient populations offers opportunities to encourage individuals to pursue a career in medicine, including pediatrics and pediatric subspecialties.…”
Section: Conclusion/discussionmentioning
confidence: 99%